The Campus Canopy, 1942-02-13 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1942)
The Campus Canopy, February 13, 1942. Vol. 8, No. 13. -- “Pine Cone” To Be Distributed Here Probably March 2 -- Martin, Johnson, Williams Win In S. G. A. Elections -- Seniors Will Hear Operas in Atlanta With Pons, Moore -- Fray - Braggiotti To Sway Boogie Woogie Lovers and High Brow Enthusiasts -- Paintings To Be Rented Are Named -- The South’s Sweetest Singers Thrill Eyes and Ears of GSWC -- First Aid Gasses Begin on Saturday Under Miss Carter
Digitized from original print, Valdosta State University Archives and Special Collections, February 14, 2017.
Keywords: The Campus Canopy; The Georgia State Woman's College; GSWC; Valdosta State College; Valdosta State University; VSC; VSU; 1940s; 1942